2013
DOI: 10.1161/hypertensionaha.111.00321
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for c-Myc in G Protein–Coupled Receptor Kinase 4 (GRK4) Transcriptional Regulation in Human Kidney Proximal Tubule Cells

Abstract: The G coupled-protein receptor kinase 4 (GRK4) negatively regulates the dopaminergic system by desensitizing the dopamine-1-receptor (D1R). The expressional control of GRK4 has not been reported, but here, we show that the transcription factor c-Myc binds to the promoter of GRK4 and positively regulates GRK4 protein expression in human renal proximal tubule cells (RPTCs). Addition of phorbol esters (PMA) to RPTCs not only increased c-Myc binding to the GRK4 promoter, but also increased both phospho-c-Myc and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…It is known that c‐Myc is a transcription factor for GRK4, and there is evidence that ROS increases c‐Myc expression . We, therefore, tried to determine whether PM 2.5 increased GRK4 via the c‐Myc pathway.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is known that c‐Myc is a transcription factor for GRK4, and there is evidence that ROS increases c‐Myc expression . We, therefore, tried to determine whether PM 2.5 increased GRK4 via the c‐Myc pathway.…”
Section: Resultsmentioning
confidence: 99%
“…c‐Myc was shown to bind to the promoter region of GRK4 in Burkitt lymphoma cells. Gildea et al found c‐Myc may be involved in the increase in blood pressure in hypertension that is mediated by increased activity of the renin‐angiotensin system and decreased activity of the renal dopaminergic system . Many other studies also report that ROS increased c‐Myc expression .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It seemed logical to also compare the mRNA expression of different GRK isoforms in aortic smooth muscle of normotensive and hypertensive animals, as PKC may play a role as a GRK regulator (Pronin and Benovic, 1997;Kohout and Lefkowitz, 2003;Lorenz et al, 2003;Gildea et al, 2013). Of the seven known isoforms of GRK reported (Gurevich et al, 2012), the mRNA expressions of GRK1 and GRK7 could not be detected in either WKY or SHR aortic smooth muscle (data not shown).…”
Section: G Protein-coupled Kinase (Grk) and Arrestinmentioning
confidence: 99%